Behavior of Grouted Sleeve Wall Connection under Lateral Load - Ling, Jen Hua; Abd. Rahman, Ahmad Baharuddin; Ibrahim, Izni Syahrizal (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2024)
A grouted sleeve’s efficiency in splicing steel bars makes it a potential choice for connecting precast elements. While most studies have focused on the feasibility of grouted sleeves under tension, only a few have investigated the real response of precast concrete members connected using grouted sleeves. In this study, Tapered Head Sleeves (THS) were utilized as connections for precast walls. The objectives were to examine their behavior under incremental lateral loads and assess the feasibility of THS as a wall connection. Five test specimens and one control specimen were fabricated, each comprising two walls joined by THS. The load was applied 1.8 m above the joint until specimen failure. Specimens that experienced bar fracture failure exhibited a relatively large drift upon failure, while those failing due to bar bond slip showed smaller drift. Factors contributing to wall drift included horizontal slip, rocking displacement, cantilever bending deformation, and compressive settlement. The ultimate load increased by 71% as the embedded length increased from 75 mm to 175 mm, and it increased by 50% as the sleeve diameter decreased from 75 mm to 50 mm. The sleeves' performance was evaluated for feasibility based on the strength ratio, drift ratio, ductility ratio, failure mode, performance ratio, serviceability ratio, and length ratio. Only THS-8 met all the criteria, suggesting that the bar's embedded length should be at least 11 times the bar diameter.